CRYPTOCURRENCIES AS A PAYMENT METHOD - Felipe Gómez Langer Kevin, Gabriel; Guerrero Gómez, Emanuel; Ramón Rojas González, Rodrigo; Arnaldo Dávalos Giménez, Luis; G. Brítez Lezcano, Liza (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this work is to study and investigate the feasibility of the application of cryptocurrencies as a payment method. The questionnaire was applied as a data collection technique where the population went to 2 sectors, 10 sales managers and 50 clients and buyers. The research was carried out with a quantitative approach. The research design is descriptive. The results obtained showed that: the majority of those surveyed have knowledge about the cryptocurrency market and what their implementation could mean for our market, they also demonstrated that they are open to this new payment method within commerce.